EVALUASI PELAYANAN KARTU KELUARGA DI DINAS CATATAN SIPIL DAN KEPENDUDUKAN KOTA MANADO - Sangkoy, Desy; Lengkong, Florence Daicy; Kiyai, Burhanuddin (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT:Based on the research conducted, it is known that there is a purpose or goal that is clear and consistent policy regarding creation of the Family Card in the Department of Population and Civil Registration Manado City; There are strong theoretical support in formulating policy making family card of Population and Civil Registration Manado City, and with the existing legal basis so as to ensure compliance of the existing employees as well as their respective duties in accordance with SOP (Standard Operating Procedure) applicable in the Department of Population and Civil Registration Manado City.This study uses qualitative research methods the Department of Population and Civil Registration Manado City. Source of data / research respondents are not quantified, as needed research. Data collection techniques using interview guide. The data analysis technique used is descriptive qualitative.Based on the results of the study concluded: that the Family Card Services the Department of Population and Civil Registration Manado City implemented or executed in accordance with the procedures / rules which apply as outlined in the SOP (Standard Operating Procedure).So that the delivery of public services to be better compared to years ago.Based on the results of the study suggested that the government Awareness society the importance of having their identity through documents Population and importance of having a family card (KK).Keywords: Evaluation, Policy, Services